P1.020 Phenotypic and Genetic Characterization of the First Three Cases of Extended-Spectrum Cephalosporin Resistant Neisseria Gonorrhoeae Infection in South Africa and Association with Cefixime Treatment Failure. (13th July 2013) - Gumede, L Y E; Unemo, M; Sriruttan, C; Golparian, D; Müller, E E; Rebe, K; Fick, D; Wet, J de; Coetzee, J; Lewis, D A
Abstract : Objectives: To describe the phenotypic and genetic characteristics of the first three cases of extended-spectrum cephalosporin (ESC) resistant Neisseria gonorrhoeae in South Africa which were associated, in one case, with a verified cefixime treatment failure. Methods: Three ESC resistant N. gonorrhoeae isolates were cultured from the urethral discharge of three men-who-have-sex-with-men (MSM), two residing in Johannesburg and one in Cape Town. One of the MSM reported a persistent urethral discharge which had failed to respond to previous therapy with oral cefixime. Agar dilution minimum inhibitory concentration assays were performed for eight antibiotics. The Johannesburg patients' isolates were further characterised by identification of key β-lactam-associated resistance mutations in penA, mtrR and its promoter, porB1b, ponA, and pilQ through PCR-based amplification and DNA sequencing . For molecular epidemiological characterisation, all three isolates were typed by N. gonorrhoeae multi-antigen sequencing typing (NG-MAST); additionally, full-length porB gene sequencing and multi-locus sequence typing (MLST) were performed for the Johannesburg isolates. Results: All three isolates were resistant to cefixime, ciprofloxacin, penicillin and tetracycline, intermediate/resistant to azithromycin but susceptible to ceftriaxone and gentamicin. The Johannesburg isolates had the type XXXIV penA mosaic allele in addition to previously described resistance mutations in the mtrR promoter (A deletion), porB1b ( penB ) (G101K, A102N) and ponA1 (L421P). All three isolates had an identical N. gonorrhoeae multi-antigen sequence type (ST4822). The two Johannesburg isolates had an identical multi-locus sequence type (ST1901). Conclusions: All three strains were resistant to cefixime and were epidemiologically linked with identical NG-MAST sequence types. The Johannesburg isolates possessed a number of key β-lactam-associated resistance mutations and the type XXXIV penA mosaic allele. These two isolates belonged to a successful international MSM-linked multi-drug-resistant gonococcal clone (MLST ST1901), associated with several cefixime treatment failures in Europe and North America.